A Cross-Sectional Observational Study On Serum Electrolyte Abnormalities During An Episode Of Neonatal Seizure At A Tertiary Care Centre In Kolar - Melasangam, Deepak; K.N , Shashidhar.; .J, Krishnappa (Journal of Neonatal Surgery, 2025)
Background: Neonatal seizures signal neurological dysfunction, affecting 1.5–14 per 1,000 live births. They often result from brain injury, with causes like HIE, stroke, bleeds, infections, and metabolic issues. Biochemical imbalances such as hypoglycemia, hypocalcemia are key contributors or consequences. This study explores the range and impact of such abnormalities in neonatal seizures. Objectives: This study aims to assess the abnormalities of electrolytes noted during an episode of neonatal seizure and determine the association between electrolyte abnormalities and occurrence of seizures in neonates. Methods: This cross-sectional study was conducted on neonates presenting with seizures at a tertiary care centre in Kolar between May 2023 and October 2024.Relevant clinical data and laboratory data was collected. The collected data underwent statistical analysis. Results: In this study of 62 neonates with seizures, females were slightly predominant (58.1%), with most being term (72.6%) and delivered via cesarean section (53.2%). Seizures commonly occurred within the first three days, peaking on day two (37%). Subtle seizures were most frequent (50%), followed by generalized tonic (29%) and multifocal clonic (11.3%). Electrolyte abnormalities were present in 66.1%, mainly hypocalcemia (37.9%) and hypernatremia (31%). Nearly half (46.8%) of seizures were clearly linked to electrolyte disturbances, underscoring the importance of routine biochemical screening in neonatal seizures. Conclusion: In this study, nearly half of neonates with seizures had electrolyte imbalances, predominantly hypocalcemia and hypernatremia. No significant association was found between seizure type and specific electrolyte abnormalities. Routine serum electrolyte evaluation is recommended for all neonatal seizures. Early detection and correction may improve outcomes and reduce recurrence.